Sensitivity of PXR to the Electric Susceptibility Near the K-edge of Ge - Preliminary Results: preprint Hiroshima University HUPD-9320 - Endo I.; Harada M.; Kobayashi T.; Lee Y. S.; Takahashi T.; Muto M.; Yoshida K.; Nitta H.; Potylitsyn A. P. Alexander Petrovich; Zabaev V. N. Viktor Nikolaevich (Hiroshima, 1993)
В фонде НТБ ТПУ отсутствует